PENGARUH DEMOGRAFI, FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, LOCUS OF CONTROL DAN FINANCIAL SELF-EFFICACY TERHADAP FINANCIAL MANAGEMENT BEHAVIOR MASYARAKAT SURABAYA - LAILI RIZKIAWATI, NUR; ASANDIMITRA HARYONO, NADIA (Jurnal Ilmu Manajemen (JIM), 2018)
This study aimed to analyze the influence of income, gender, age, financial knowledge, financial attitude, a locus of control and financial self-efficacy on financial management behavior of Surabayas citizen. This type of research is quantitative and conclusive research in the form of causality. The data that be in this research, taken from interview and questionnaire with the 215 respondent. The data analysis technique used multiple linear regression and using IBM SPSS version 24. The result showed that the only locus of control and financial self efficacy significantly effect on financial management behavior, while income, gender, age, financial knowledge, and financial attitude dont have any effect on financial management behavior. Income doesnt have an effect on financial management behavior due to lack of research limits in determining the criteria of respondents, such as marital status, the number of dependents and other. Gender doesnt have an effect on financial management behavior because both women and men have an equal opportunity to financial management wisely. Age doesnt have an effect on financial management behavior because the respondents in this study consisted of various age, as long as still have income hence both young age and old age have an opportunity to financial management wisely. Financial knowledge doesnt have an effect on financial management behavior because respondents in this study have a different background, so the financial knowledge owned also different. Financial attitude doesnt have an effect on financial management behavior because there are differences among respondents to respond financial situation. Keywords: Financial management behavior, demography, financial attitude, locus of control, financial self-efficacy